Sosialisasi PSBB, perwako dalam rangka upaya pencegahan Covid-19 di Pekanbaru dan kaitannya dengan hak kesehatan masyarakat - Mukhlis Mukhlis; Hayatul Ismi; Emilda Firdaus; Maria Maya Lestari; Adlin Adlin (Unri Conference Series: Community Engagement, 2020)
With the increasing number of Covid-19 cases in Indonesia, including in Riau Province, it is necessary to implement Large-Scale Social Restrictions (PSBB). PSBB is one way to reduce the impact of Covid-19. PSBB has currently been implemented in 10 regions in Indonesia as part of efforts to prevent the corona virus. The Central Government through the Ministry of Health has approved Pekanbaru to implement the PSBB. The main reason for implementing PSBB in dealing with the Covid-19 corona virus is because physical distancing, which has been carried out so far, is ineffective in the community. On that basis, the government strengthened the policy of physical restrictions for the community by implementing PSBB in the regions. It is necessary to do the socialization of PSBB and this Perwako, so that the public knows the Rules about PSBB. The service activity aims to provide guidance to the people of Pekanbaru City regarding Corona and PSBB, because Pekanbaru City is one of the cities that is a transit point. The implementation of activities to increase public knowledge about PSBB and Perwako was successful. This can be seen from changes in the behavior of people who were previously reluctant to wear masks, then have started wearing masks when they go out, as can be seen from the behavior of people who have avoided people's hassles and tried to keep their distance. The community also complies with large-scale social restrictions set by the government, this can be seen from the minimum community activity at night outside the home.